The Role of Augmented Reality in Enhancing Social Business Models: a Pathway to Sustainable Development - Guilin, Xie; Jiao, Deng; Wang, Yuanyuan (Yayasan Adra Karima Hubbi, 2024)
Augmented reality (AR) technology has emerged as a powerful tool in various sectors, offering innovative solutions that enhance user engagement and experience. In the context of social business models, AR has the potential to drive sustainable development by addressing key social and environmental challenges. Despite its growing popularity, the role of AR in enhancing social business models remains underexplored. This research aims to investigate the impact of augmented reality on social business models and its potential to contribute to sustainable development. The study seeks to identify how AR can be integrated into social enterprises to enhance their effectiveness and sustainability. The research employs a mixed-methods approach, combining quantitative surveys and qualitative case studies. A survey was conducted with 150 social entrepreneurs to gather data on the use of AR and its perceived impact. Additionally, five in-depth case studies of social enterprises utilizing AR were conducted to provide detailed insights into implementation strategies and outcomes. The findings indicate that AR significantly enhances the effectiveness of social business models by improving user engagement, education, and operational efficiency. Social enterprises using AR reported higher levels of community engagement and greater impact on their social and environmental goals. The case studies revealed successful strategies for integrating AR, such as interactive educational content and immersive storytelling, which contributed to achieving sustainable development outcomes. The study concludes that augmented reality holds substantial potential for enhancing social business models and promoting sustainable development. By leveraging AR technology, social enterprises can create more engaging and impactful solutions to address social and environmental challenges. Continued research and investment in AR applications within the social enterprise sector are recommended to fully realize its potential.